Effect of carbon nanotexture on the synthesis, initial growth mechanism and photoluminescence properties of SiC nanowires. (1st December 2020) - Xie, Xiangmin; Su, Zhe'an; Huang, Dong; Yang, Cheng; Wang, Yafeng; He, Kejian; Huang, Qizhong
Abstract: Although the spontaneous vapor–solid growth of SiC nanowires is a well-established phenomenon, the exact mechanism by which nanowires grow on substrates is still poorly understood. Here, we studied the initial growth of SiC nanowires on carbon sources with different nanotextures via a catalyst-free vapor reaction between a polyacrylonitrile-based carbon fiber and a silicon powder. The results revealed that the SiC nanowires were preferentially formed on the carbon fiber with a higher degree of graphitization. Detailed analyses suggested that the growth behavior of the underlying SiC film formed on the carbon fibers, which is strongly affected by the microstructures of the carbon fibers, plays an important role in the formation of nanowires. In addition, the photoluminescence spectrum of SiC nanowires showed strong ultraviolet–visible emission peaks at an excitation wavelength of 250 nm, which may provide potential applications in the field of optoelectronic devices.